Antioxidant and antimicrobial properties of polysaccharides from rice brans - Siriluck Surin (2018)
© 2018, Chiang Mai University. All rights reserved. Four varieties of rice bran [Khao Dawk Mali 105 (KDML), Kor Kho 6 (RD6), Sanpatong 1 (SPT) and Kum Doi Saket] were pretreated with solvents (ethanol and hexane) and the chemical composition, structure, antioxidant and antimicrobial properties of the extracted (crude) polysaccharides were investigated. The polysaccharides contained five functional groups: alkane, alkene, amine, carbonyl and hydroxyl. However, the nature of the solvent and rice bran variety significantly (P < 0.05) effected the polysaccharide chemical composition. Polysaccharides extracted by hexane possessed high antioxidant activity. Kum Doi Saket had the highest polysaccharide content and antioxidant activity. The amount of Kum Doi Saket polysaccharide required to reduce 50% of 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2-azino-bis (3-ethylbenzthiazoline-6-sulphonate) (ABTS) radicals (IC50value) were in the range 1.1-5.2 and 0.6-1.8 mg/mL, respectively. The ferric-reducing antioxidant power (FRAP) of Kum Doi Saket polysaccharide ranged from 28.8-194.4 μmol Fe2+/g. Moreover, the polysaccharides inhibited the pathogenic bacteria, Staphylococcus aureus and Escherichia coli.